2020
DOI: 10.1177/1534734620907978
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Autologous Stromal Vascular Fraction Cells and Platelet-Rich Plasma for Chronic Ulceration of the Diabetic Lower Limb Improves Wound Healing

Abstract: The discovery of stromal vascular fraction cells and platelet-rich plasma in promoting tissue regeneration has prompted a new idea for the treatment of chronic diabetic ulcer of the lower limb. The study aim was to evaluate the clinical efficacy of a new method that applied stromal vascular fraction cells and platelet-rich plasma together in the treatment of recalcitrant chronic diabetic ulcer. We conducted a single-center, prospective, open, noncontrolled study. Four patients (5 ulcers in total) who had recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Interestingly, both PRP and SVF application have been proposed in recent years to improve wound healing [43][44][45]. Yin et al proposed that the synergistic effects of PRP and SVF promote a safe and effective wound healing in chronic ulcers in humans [46]. Our data suggest that the combination of the two regenerative approaches can be accomplished in the dog.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, both PRP and SVF application have been proposed in recent years to improve wound healing [43][44][45]. Yin et al proposed that the synergistic effects of PRP and SVF promote a safe and effective wound healing in chronic ulcers in humans [46]. Our data suggest that the combination of the two regenerative approaches can be accomplished in the dog.…”
Section: Discussionmentioning
confidence: 57%
“…Of these, 77 articles were selected after reading the titles and abstracts and removing duplicates. Then, 15 studies were removed because they met the exclusion criteria, leaving 62 studies [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] ]. ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that PRP promotes the proliferation of NP cells, facilitates the anabolic actions and migration of different cell types, and provides a favorable microenvironment for the regeneration and repair of various soft tissues. 21 , 22 The study by Chen et al 23 cultured human NP cells in PRP and found that PRP could enhance cell proliferation and differentiation through transforming growth factor beta-1, demonstrating for the first time that PRP is a therapeutic option for preventing disc degeneration. In a study of 47 patients with lumbar disc degeneration, Tuakli-wosornu et al 12 found significant improvements in Functional Rating Index, Numerical Rating Scale of Pain, and North American Spine Society satisfaction scores in participants who received intradiscal PRP compared with those who received contrast alone.…”
Section: Discussionmentioning
confidence: 99%